Ikimokyklinio amžiaus vaiko raida: žaidimas ir savireguliacija : monografija - Hakkarainen, Pentti Ensio (Vytautas Magnus University, 2015)
Monografijoje nagrinėjama ikimokyklinio amžiaus kultūrinė vaiko raida ir siekiama aptarti vaiko menamo žaidimo ir savireguliacijos bendro žaidimo metu sąsajas. Teoriniu lygmeniu analizuojami svarbiausi kultūrinės-istorinės psichologijos pagrindu plėtojamos žaidimo teorijos aspektai ir suformuluojami pagrindiniai savireguliacijos formavimosi žaidybinėje veikloje principai. Praktiniu lygmeniu pateikiama tyrėjų sukurta naratyvinio žaidimo programa ir jos pagrindu atliktų intervencijų rezultatai. Tyrimo rezultatai leidžia teigti, kad išvystytas ir kokybiškai aukšto lygmens žaidimas sudaro prielaidas savireguliacijos vystymuisi. The idea to write this book primarily came from our intention to share what we have discovered about one of the greatest childhood miracles - play. For a number of years we have explored this phenomenon, yet its profound and extraordinary nature still continues to surprise us. Promotes development and, at the same time, is the greatest achievement of the child. Keeping this in mind, we designed our monograph for a few purposes. First, we wanted to present the results of the three-year project "Development of Self-Regulation in Play" attained in play research laboratory of the Lithuanian University of Educational Sciences. Second, we sought for the first time to discuss in Lithuanian language the theory of play based on cultural - historical psychology. Our objective was to formulate and present the key principles of the development of self-regulation through play activities. Finally, we aimed to describe the steps of practical use of joint (adult-child) play activities that help a child to develop a self-regulatory behavior during play.